(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
One of the current problems in rheumatology is microcrystalline arthritis.This article describes calcium pyrophosphate arthropathies, their specific etiology, classification, clinical course, and diagnostic methods.